Pesantren dan Toleransi Beragama - Muntahibun Nafis (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Historically, the existence of Islamic boarding school has changed. There are differences among Islamic boarding schools where all the boarding schools attempt to show their excellence and development from time to time. One of the developments is religious relationship in which the Islamic boarding school becomes more inclusive to the surrounding. In this case, morality and tolerance values are cultivated among the members of the boarding school so that a harmonious life can be achieved. In addition, redefining the concept of rahmatan li al ‘alamin ( bless for the universe) and ukhuwah (brotherhood) is of importance to strengthen tolerance.